Die "Judendeportationen" aus dem Deutschen Reich 1941 - 1945 : eine kommentierte Chronologie - Gottwaldt, Alfred B. 1949-2015 (Marixverlag, 2005)
Auch Deportationen aus: Aschersleben, Bernburg, Bitterfeld, Blankenburg, Dessau, Eisleben, Gardelegen, Halberstadt, Halle (Saale), Klostermansfeld, Köthen, Magdeburg, Merseburg, Naumburg, Querfurt, Raguhn, Roßlau, Sangerhausen, Staßfurt, Stendal, Weißenfels, Wernigerode, Zeitz